Coral distribution in inshore reefs within Kuantan coastal waters - Mohd Hanapiah, Muhammad Faiz; Saad, Shahbudin; Ahmad, Zuhairi; Azmi, Amira Nasuha (2020)
Inshore reefs areas play several important ecosystem functions in marine environment especially in coastal area. Eight reef locations were surveyed using coral video transect (CVT) technique between April 2017 and April 2019 in Balok reef and Raja Muda reef to estimate coral reef benthic components. Physicochemical parameters (sea temperature, salinity and pH) were measured from March until September 2018 while current speed was measured using Acoustic Doppler Current Profiler (ADCP) between August 2017 and October 2018. Data analysis on coral reef benthic components indicated that Kuantan coastal area has ‘fair’ coral cover with average percentage of 40.2 % ± 10.65. Angly 3 (ST3) recorded the highest live coral cover coverage with 50.3%. Abiotic components (sand and rock) were the second-most abundant and the coverage of dead coral was relatively low at all stations. A total of 33 coral genera was recorded in this study in which Porites mean percentage cover dominated most of the reef sites. Physicochemical data recorded in the inshore reef were within acceptable range with previous study on island reef although current flow was relatively higher. The present findings provided important assessment on coral distribution pattern in Kuantan coastal waters.